Towards a Pragma-Semiotics of Ritual(ized) Gesture and Performance - Blanariu, Nicoleta Popa (Arte, Individuo y Sociedad, 2018)
This paper analyzes some ritual and performing phenomena from different cultures, by using a unifying pragma-semiotics approach, especially the speech acts theory. Claude Lévi-Strauss (1995) refers to the rites as a “paralanguage”. In our opinion, his taxonomy of ritual praxis is reducible to the dichotomy constative/performative introduced by John L. Austin (1962), that he later reconsiders and transforms into the trichotomy locutionary / illocutionary / perlocutionary. In Austin’s opinion, the speech acts theory is part of a theory of action. We aim to explain that this is confirmed not only in the very linguistic act of utterance, but also in the multimodal expression (movement, gesture, word, incantation, costumes, accessories) specific to some ritual(ized) social contexts, particularly ritual performances. Like verbal performative utterances, ritual(ized) gesture and movement may have real and immediate efficiency, which means that it may produce a real-world change, from the participant’s viewpoint. Without a ritual context, the choreo-dramatic expression loses its pragmatic function – that of “modification” of the real (Lévi-Strauss, 1995). However, it manifests a different one, essentially “aesthetic”. From our point of view, the illocutionary ritual act is thus replaced by a “fictional act”, a category which was previously described by both John R. Searle (1982) and Gérard Genette (1991).